2016
DOI: 10.1039/c6tb01285j
|View full text |Cite
|
Sign up to set email alerts
|

A facile approach for thermal and reduction dual-responsive prodrug nanogels for intracellular doxorubicin delivery

Abstract: Temperature and redox dual responsive prodrug nanogels for controlled drug release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The concentration of reducing GSH in the cytosol is ≈2 × 10 −3 –10 × 10 −3 m as compared to the extracellular fluids having ≈2 × 10 −6 –20 × 10 −6 m . Hence, drug delivery vehicles comprised of disulfide bonds are particularly interesting due to their characteristic degradation under physically relevant reducing conditions …”
Section: Microgels For Drug Delivery Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentration of reducing GSH in the cytosol is ≈2 × 10 −3 –10 × 10 −3 m as compared to the extracellular fluids having ≈2 × 10 −6 –20 × 10 −6 m . Hence, drug delivery vehicles comprised of disulfide bonds are particularly interesting due to their characteristic degradation under physically relevant reducing conditions …”
Section: Microgels For Drug Delivery Applicationmentioning
confidence: 99%
“…The cargo can be released finally at the targeted site by the destruction of the chemical bond in the presence of stimuli. Peng et al reported the conjugation of DOX by taking advantage of reactive succinimide groups present in PVCL‐ co ‐ N ‐succinimidyl methacrylate microgels that can be degraded under acidic medium . Similarly, acid‐labile Schiff linkage have been used for conjugating doxorubicin to the carrier system and the loaded drug can be released at low pH by hydrolysis of these bonds .…”
Section: Microgels For Drug Delivery Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…[40b] The distribution of succinimidyl groups to functionalize microgels was visualized by reaction with Alexa Fluor 647 Cadaverine, which revealed that the succinimidyl functionalities were mainly in the outer regions of the microgels due to the corresponding synthesis of the microgels. [41] Furthermore, polymer nanoparticles were investigated by Tian et al using a PALM-like approach, which they called "photo actuated unimolecular logical switching attained reconstruction" (PULSAR) nanoscopy. [42] For this, the PS core of the core-shell nanoparticles was labeled with a spiropyran photoswitch.…”
Section: Polymer Microgels/nanogels and Nanoparticlesmentioning
confidence: 99%